A Bibliometric Analysis of Critical and Creative Thinking in Elementary School Mathematics Learning - Aswin; Al Jupri; Dadang Juandi; Suhendra; Eyus Sudihartinih; Andi Sri Hardiana (Hipotenusa: Journal of Mathematical Society, 2026)
Through a bibliometric approach, this study aims to analyze trends, main focuses, and potential future research themes related to critical and creative thinking skills in mathematics learning at the elementary school level. The data were obtained from the Scopus database covering the years 1997–2025 with the search keywords "critical thinking" OR "creative thinking" AND math* AND "elementary school", resulting in 125 documents analyzed using Biblioshiny R and VOSviewer software. The analysis results show that publications on this topic have increased significantly since 2016, with Indonesia having the highest number of publications. However, the United States and Taiwan dominate in terms of citation impact. Four main clusters were identified: innovative learning approaches (including STEM and problem-based learning), elementary education contexts, curriculum development and engineering education, and strengthening critical thinking skills through geometry and problem solving. Bibliometric visualization also shows that topics such as "creative thinking", "teaching and learning", and "educational computing" are growing and promising areas for further research. This study recommends integrating interdisciplinary and technological approaches in curriculum development and the need for increased international collaboration to strengthen research impact. These findings provide an important contribution to mapping the scientific landscape and the direction of developing mathematics learning that fosters higher-order thinking skills from an elementary school.